Regional Harmonisation of Contract Law - Is It Feasible? - Zeller, Bruno (Journal of Law, Society and Development, 2016)
This article investigates whether regional harmonisation is merely an academic exercise or a serious attempt to create a uniform contract law in a defined region. It builds on the recently conducted Symposium at Villanova University in 2013 and addresses comparatively the efforts by well-defined regions, namely OHADA, the EU and ASEAN. OHADA has introduced regional uniform laws; the EU is still working on formulating them. Furthermore, UNCITRAL has considered a proposal by the Swiss government to work urgently on a new initiative to further harmonise contract law. Against this backdrop, this article argues that regional proposals to harmonise contract law are akin to saying that ‘ein Gespenst geht um’ (a ghost is going around) (Reich 2006: 425). This is justified, because a proposal to create a harmonised contract law in East Asia has currently also been discussed, but the discussions have stalled. Is there a solution or do we simply admit that regional harmonisation is not possible? The starting point is the CISG, as has been adopted by 80 countries and needs to be considered by any region as a possible, albeit not perfect, solution. If the CISG has already been ratified, the issue, then, is how any regional developments can coexist with it. Or does a ratification of the CISG preclude any regional harmonisation? Secondly, the question must be asked whether regional harmonisation will reduce transaction costs, which is beyond what the CISG was able to achieve. This article argues that as far as the drafting of international instruments isconcerned, a shift in thinking has occurred. Instruments such as the Cape Town Convention are considered to be reforming the law in a particular narrow area rather than attempting to draft codes. Furthermore, the process is driven by industry groups. Regional harmonisation must take note of the ongoing shift and a more fruitful approach is to develop uniform laws through a better understanding and coordination of existing instruments.
Keywords: CISG; Contract law; Regional harmonisation; Uniform law